Strategies used in improving and assessing the level of reporting of implementation fidelity in randomised controlled trials of palliative care complex interventions: A systematic review. (February 2018) - Ang, Kexin; Hepgul, Nilay; Gao, Wei; Higginson, Irene J
Background: Implementation fidelity is critical in evaluating effectiveness of interventions. Aim: Identifying and summarising strategies to improve and assess the level of reporting of implementation fidelity in randomised controlled trials of palliative care complex interventions. Design: Systematic review. Data sources: Published and completed randomised controlled trials from 2000 to current evaluating effectiveness of specialised palliative care services on patient-centred outcomes in adult patients were examined. MEDLINE was searched from 2008 to 29 September 2015 and supplemented by randomised controlled trials identified in a 2008 systematic review. Results: Altogether, 20 randomised controlled trials involving 8426 patients were reviewed using 40 subcomponents of five elements of implementation fidelity (resulting in 20 × 40 = 800 items). Over 88 strategies were identified, classified under the following elements: 'treatment design', 'training providers', 'delivery of treatment', 'receipt of treatment' and 'enactment of treatment skills'. No single overarching strategy was discovered. Strategies under 'treatment design' aimed to ensure equivalent treatment dose between and within intervention and control groups, and delivery of necessary ingredients. Ongoing 'training (of) providers' included supervision and ensuring skill acquisition. Use of treatment manuals and implementation checklists aimed to aid 'delivery of treatment'. Research teams aimed to improve 'receipt of treatment' by transmitting clear information and verifying understanding, while improving 'enactment of treatment skills' by reviewing and reinforcing prior content. Only 26% of the items received sufficient reporting; 34% were either not used or reported on. Conclusion: Implementation fidelity in palliative care is under-recognised. A table to collate these strategies to improve implementation fidelity in palliative care research and clinical practice is proposed.